2005
DOI: 10.1002/art.21162
|View full text |Cite
|
Sign up to set email alerts
|

Severe valvular regurgitation and antiphospholipid antibodies in systemic lupus erythematosus: A prospective, long-term, followup study

Abstract: Objective. To assess whether the presence of antiphospholipid antibodies is related to the incidence and progression of severe valvular dysfunction and the need for valve replacement in patients with systemic lupus erythematosus (SLE). Methods. In this prospective, long-term followup study, the initial echocardiographic findings in a cohort of 61 consecutive SLE patients were compared with those of 40 matched controls. All patients were serially evaluated for 14 ؎ 3 years and had a followup echocardiogram 8 ؎ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
72
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 37 publications
3
72
1
2
Order By: Relevance
“…9 The associated link of antiphospholipids with lupus is wellknown 11,12 and helps provide an additional mechanism of injury to the cardiac valve as seen in Libman-Sacks endocarditis, possibly one of deposition of immunoglobulin and complement. 13 Studies of echocardiographic findings when compared with anticardiolipin and antiphospholipid antibody titers have shown significant correlation for more severe valve dysfunction with increasing titers. 8,11 [var vr_print_hyperlink]Our patient's white blood cell count was normal on admission and decreased during the course of her hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The associated link of antiphospholipids with lupus is wellknown 11,12 and helps provide an additional mechanism of injury to the cardiac valve as seen in Libman-Sacks endocarditis, possibly one of deposition of immunoglobulin and complement. 13 Studies of echocardiographic findings when compared with anticardiolipin and antiphospholipid antibody titers have shown significant correlation for more severe valve dysfunction with increasing titers. 8,11 [var vr_print_hyperlink]Our patient's white blood cell count was normal on admission and decreased during the course of her hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…A previous C3 level 1 year before admission was within the normal range at 113 mg/dL. A quantitative assay of rheumatoid factor was 10 (range [10][11][12][13][14]. The erythrocyte sedimentation rate (ESR) was 106 mm/h (range 0-20 mm/h) and C-reactive protein (CRP) was elevated at 11.4 mg/dL (range <0.9 mg/dL).…”
mentioning
confidence: 99%
“…This is not a surprising finding since correlation between severity of lupus and presence of cardiac involvement has not been demonstrated in other studies. 13,15 The potential cardiac toxicity of both autologous and allogeneic HSCT in patients with hematological malignancies and cardiac co-morbidities has been reported for decades, 5,16,17 with poor pre-transplant LVEF being associated with a higher incidence of cardiac morbidity and mortality in some studies. 18 As a result, patients with hematological malignancies and coexistent significant cardiac dysfunction are precluded from transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The association between APS and severity of valvular dysfunction has been reported. Perez-Villa et al 15 demonstrated that worsening valve function and eventual need for valve surgery were associated with higher anticardiolipin antibody titers, but not with activity of SLE. Since we had reported previously on induction of remission from APS among patients with SLE undergoing HSCT, 29 it is possible that this reduction in antiphospholipid antibodies may account for the improvement in valvular function observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation